Implementasi Teori Belajar Behavioristik dalam Pembelajaran Pendidikan Pancasila dan Kewarganegaraan di Sekolah Menengah Pertama - Wulandari, Seli Dina; Prasetiyo, Wibowo Heru (JPK (Jurnal Pancasila dan Kewarganegaraan), 2023)
The purpose of this research was to find out the various characteristics that were identified during the learning process and to find out how the behavioristic characteristics were identified in learning Pancasila and Citizenship Education at SMP Muhammadiyah 7 Surakarta. The method used in this study is a descriptive qualitative method. This research’s data and sources are in the form of stimulus responses from teachers and students of class VII B SMP Muhammadiyah 7 Surakarta. This research uses interview instruments and observation instruments. Data collection techniques used in this study were interviews and observation. The results of the study show that the behavior that appears in Civics learning consists of two responses, namely verbal and nonverbal responses. The verbal response identified student behavior: mentioning, answering, asking, conveying, responding, and commenting. Nonverbal responses to student behavior identified were students recording, compiling, and changing the wrong writing according to the stimulus at each stage of the learning carried out. In addition, the behavioristic characteristics identified during Civics learning are seen in several ways, namely positioning students as passive individuals, causing or showing the expected behavior, viewing knowledge as something stagnant and cannot be changed which results in the delivery being the same every year. , and views teaching as simply a transfer of knowledge and learning as a process of acquiring knowledge